Study on Invasive Procedures of the Chest Lesions: Are they Must be Performed and Why? - A. Hilendarov; A. Georgiev; A. Chervenkov (Issues and Development in Health Research Vol. 4, 2021)
Introduction: Lung cancer is one of the most common causes of mortality worldwide. An increasing number of lung and mediastinal lesions are found by MDCT, and histological identification is frequently required to determine the best treatment option for these lesions. At this article we have the aims to describe the invasive procedures of the chest lesions - indications, contraindications, technical aspects, and diagnostic accuracy of the percutaneous lung biopsies. Methods: In patients with lung lesions, fine-needle aspiration biopsy (FNAB) and core-needle biopsy (CNB) are the methods of choice for collecting tissue specimens.Treatment procedures are frequently based on histology diagnosis. When logistically feasible or when other procedures (such as bronchoscopy with lavage) are equivocal, FNAB biopsy is performed in 85 of the 97 patients in our study, and CNB is performed in 12 of the 97 patients. The needles used were 19-22G disposable needles. Results: FNAB under CT control was conducted on all 76 patients, ages 21 to 79, who had lung lesions with a diameter of 2.0 cm or less. Due to the superficial localisation of the lesions, FNAB under US control is performed in 13 patients. All patients have their tissues samples analysed cytologically and histologically.The diagnostic sensitivity and accuracy, as well as the type of complications that occurred, are calculated. CNB showed a small improvement in overall sensitivity, specificity, and accuracy. Conclusion: Percutaneous FNAB and CNB are the safe procedures for diagnostic evaluation of focal pulmonary lezions. The complications are rare: pneumothorax, pulmonary haemorrhage but some, like air embolism and metastatic seeding are with severe consequences.